The role of national innovation culture in the globalized world - Lažnjak, Jasminka (Array, 2010)
The paper deals with the problem of innovation culture on the national level in the age of globalized science, technology and innovation trying to answer the question why some societies are more innovative than others and do existing cultural conditions determine when, how and in what form innovation will be adopted? Higher innovation capacity is associated with societies characterized by higher individualism, willingness to take risks, readiness to accept change, long- term orientation, low power distance, weak uncertainty avoidance, openness to new information, value of education to society, positive attitudes toward science. In the paper are presented preliminary results of the survey on the representative sample of Croatian population. Croatian national innovation culture of Croatia is operationalized as set of value orientations and norms like attitudes toward innovation, egalitarianism, statism, uncertainty avoidance, individualism, masculinity - femininity, long-term or short-term orientation, and power distance. Drawing on Hofstede's (2001, 2004) dimensions of national cultures and their application on innovation culture, Croatian survey uses different indicators but referring to the same concept of innovation culture (Didero et al. 2008 ; Jucevičius 2007). Relatively low innovative capacity in Croatian society is associated with the significant presence of traditional set of values and low trust in institutions.